PENILAIAN JENIS MULTIGEAR PADA USAHA PERIKANAN TANGKAP SKALA KECIL DI PERAIRAN SUNGSANG KABUPATEN BANYUASIN SUMATERA SELATAN - . Fauziyah; Fitri Agustriani; Bakti Satria; Apriansyah Putra; Welly Nailis (Bogor Agricultural University, 2018)
ABSTRACT Multigear has been commonly used in small-scale fishery activities in Sungsang waters. The aim of using the multigear is to enable the fishermen carry out their activities at every catching season. Inaccurate and inefficient use of the multigears are the concern that will present inefficiency or even conflict among the fishermen. Therefore the research was carried out with the objective to determine the best type of a multigear that will be used in the small scale fishery at Sungsang waters based on economic, productivity, social and biological aspects. Multiple Criteria Analysis (MCA) is the method of assessment on the quality type of the multigear. The outcome of the research presented that the best quality type of the multigear is 1) the multigear type with the combination of trammel net and drift longline; 2) the multigear type with the combination of drift gillnet (mesh, 3 inches) and drift long line; 3) the multigear type with the combination of drift gillnet (mesh, 2 inches) and trammel nets. Key Words: MA analysis, small-scale fishery, the best quality multigear,ABSTRAKMultigear telah banyak digunakan pada usaha perikanan tangkap skala kecil di Perairan Sungsang. Tujuan penggunaan multigear adalah dikarenakan agar nelayan dapat terus melakukan aktivitas penangkapan dalam setiap setiap musim penangkapan. Penggunaan multigear yang tidak tepat dan bijak, dikhawatirnya malah akan menimbulkan inefisiensi atau bahkan menimbulkan konflik antar nelayan. Oleh kerana itu, penelitian ini dilakukan dengan tujuan untuk menentukan jenis multigear unggulan pada usaha perikanan tangkap skala kecil di Perairan Sungsang berdasarkan aspek ekonomi, aspek produktivitas, aspek sosial, dan aspek biologi. Penilaian keunggulan jenis multigear menggunakan metoda Multiple Criteria Analysis (MCA). Hasil penelitian menunjukkan bahwa jenis multigear unggulan adalah: 1) jenis multigear dangan kombinasi jaring udang dan rawai hanyut; 2) jenis multigear dangan kombinasi jaring insang hanyut (mesh, 3 inci) dengan rawai hanyut (umpan), dan 3) jenis multigear dengan kombinasi jaring insang hanyut (mesh, 2 inci) dan jaring udang. Kata kunci: MCA analysis, perikanan skala kecil, multigear unggulan